The "windfall profits 2.0" during the third phase of EU-ETS - Jean-Philippe Nicolai; Jorge Zamorano (ETH Zurich, CER-ETH - Center of Economic Research, 2014)
The first two phases of the EU-ETS were characterized by a profit increase, which was primarily due to free allowances given through grandfathering. To avoid these windfall profits and to decrease leakage, two major modifications have been implemented for the third phase: electric companies no longer receive free allowances, while energy intensive and trade exposed sectors are granted free allowances that are calculated based on firm production capacity. This paper theoretically shows a new type of profit increase in sectors that are not exposed to international competition. This paper also illustrates the profit increase for the third phase of the EU-ETS and shows that profits in the electricity sector may increase by approximately 2% when free allowances are given to the other sectors.
Keywords: F18; H2; Q5; 330; Tradable permits; Oligopoly markets; Output-based allocation; EU-ETS